Theory of visual attention (TVA) applied to rats performing the 5-choice serial reaction time task: differential effects of dopaminergic and noradrenergic manipulations. - Hervig, Mona El-Sayed; Toschi, Chiara; Petersen, Anders; Vangkilde, Signe; Gether, Ulrik; Robbins, Trevor W. (Psychopharmacology, 2023)
Rationale: Attention is compromised in many psychiatric disorders, including attention-deficit/hyperactivity disorder (ADHD). While dopamine and noradrenaline systems have been implicated in ADHD, their exact role in attentional processing is yet unknown. Objectives: We applied the theory of visual attention (TVA) model, adapted from human research, to the rat 5-choice serial reaction time task (5CSRTT) to investigate catecholaminergic modulation of visual attentional processing in healthy subjects of high- and low-attention phenotypes. Methods: Rats trained on the standard 5CSRTT and tested with variable stimulus durations were treated systemically with noradrenergic and/or dopaminergic agents (atomoxetine, methylphenidate, amphetamine, phenylephrine and atipamezole). TVA modelling was applied to estimate visual processing speed for correct and incorrect visual perceptual categorisations, independent of motor reaction times, as measures of attentional capacity. Results: Atomoxetine and phenylephrine decreased response frequencies, including premature responses, increased omissions and slowed responding. In contrast, methylphenidate, amphetamine and atipamezole sped up responding and increased premature responses. Visual processing speed was also affected differentially. Atomoxetine and phenylephrine slowed, whereas methylphenidate and atipamezole sped up, visual processing, both for correct and incorrect categorisations. Amphetamine selectively improved visual processing for correct, though not incorrect, responses in high-attention rats only, possibly reflecting improved attention. Conclusions: These data indicate that the application of TVA to the 5CSRTT provides an enhanced sensitivity to capturing attentional effects. Unexpectedly, we found overall slowing effects, including impaired visual processing, following drugs either increasing extracellular noradrenaline (atomoxetine) or activating the α1-adrenoceptor (phenylephrine), while also ameliorating premature responses (impulsivity). In contrast, amphetamine had potential pro-attentional effects by enhancing visual processing, probably due to central dopamine upregulation.